The Impact of Leadership and Psychosocial Work Environment on Recipient Satisfaction in Nursing Homes and Home Care - Lundgren, Dan (Gerontol Geriatr Med, 2019)
This study examines the association between nursing assistants’ assessment of leadership, their psychosocial work environment, and satisfaction among older people receiving care in nursing homes and home care. Cross-sectional surveys were conducted with nursing assistants (n = 1,132) and people receiving care (n = 1,535) in 45 nursing homes and 21 home care units. Direct leadership was associated with the psychosocial work environment in nursing homes and home care. Furthermore, better leadership was related to higher satisfaction among nursing assistants and older people in nursing homes. Thus, indirect leadership had no effect on recipients’ satisfaction in either nursing homes or home care. The path analysis showed an indirect effect between leadership factors and recipient satisfaction. The findings suggest that the psychosocial work environment of nursing assistants and recipient satisfaction in nursing homes can be increased by improving leadership.